2017
DOI: 10.1017/laq.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Interregional Obsidian Exchange During the Late Initial Period and Early Horizon: New Perspectives From Campanayuq Rumi, Peru

Abstract: Campanayuq Rumi is a large civic-ceremonial center located in the south-central highlands of Peru. Founded in the late Initial Period (1100–800 BC), Campanayuq Rumi became an important center within the Chavín Interaction Sphere in the Early Horizon (ca. 800–400 BC). In particular, Campanayuq Rumi is significant because of its geographical proximity to Quispisisa, the most important and widely circulated obsidian source during the Early Horizon. Portable X-ray florescence (pXRF) was used to geochemically sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…We could not determine the directionality of gene flow due to a lack of very ancient South Peru Highlands individuals (Cuncaicha is further south than our later South Peru Highlands series and has ancestry more consistent with later Titicaca Basin individuals). A speculative possibility is that this admixture relates to the archaeologically documented Chavin sphere of influence ( Burger, 2019 ) that involved cultural interaction between the North Peru Highlands (Ancash) to at least the Ayacucho region (“ SouthPeruHighlands ” in this study) ∼2,900–2,350 BP as reflected in the exchange of goods like cinnabar and obsidian, and by a widespread shared material culture style manifest across the Central Andes between Jaen in the north and Ayacucho in the south and along the north-central Pacific coast ( Burger, 2008 , Burger, 2019 , Matsumoto et al., 2018 ). This scenario does not imply that the gene flow must have originated from Chavin, but that increased cultural and material exchange between the regions was accompanied by gene flow in one or both directions, although future work is necessary to test this hypothesis.…”
Section: Resultsmentioning
confidence: 95%
“…We could not determine the directionality of gene flow due to a lack of very ancient South Peru Highlands individuals (Cuncaicha is further south than our later South Peru Highlands series and has ancestry more consistent with later Titicaca Basin individuals). A speculative possibility is that this admixture relates to the archaeologically documented Chavin sphere of influence ( Burger, 2019 ) that involved cultural interaction between the North Peru Highlands (Ancash) to at least the Ayacucho region (“ SouthPeruHighlands ” in this study) ∼2,900–2,350 BP as reflected in the exchange of goods like cinnabar and obsidian, and by a widespread shared material culture style manifest across the Central Andes between Jaen in the north and Ayacucho in the south and along the north-central Pacific coast ( Burger, 2008 , Burger, 2019 , Matsumoto et al., 2018 ). This scenario does not imply that the gene flow must have originated from Chavin, but that increased cultural and material exchange between the regions was accompanied by gene flow in one or both directions, although future work is necessary to test this hypothesis.…”
Section: Resultsmentioning
confidence: 95%
“…As exchange with the Chavín interaction sphere shifted over time (Matsumoto et al . 2013), it seems plausible that different pigment sources were exploited, especially for the colour red. According to our study, the use of cinnabar-based red on ceramics was limited to Chavinoid early Paracas ceramics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The sources of some the Group D rocks are still unknown. However, several natural deposits at Quispisisa and Puzolana, located at Ayacucho, are the best-documented and closest obsidian supply (Matsumoto et al, 2018;Giesso et al, 2020). A few obsidian samples (n = 4) from layers XII-XIII analyzed using XRF and NAA methods showed that two artifacts come from Quispisisa, and another two from Puzolana (Burger & Asaro, 1979, 1993Burger & Glascock, 2000: pp.…”
Section: Materials Analysis and Observationsmentioning
confidence: 99%